206 Longevity of Deep Brain Stimulation Batteries at a Tertiary Neurosurgical Centre. (28th February 2022) - Saad, M.; Morris, R.; Rudwick, C.
Abstract: Introduction: Deep brain stimulation (DBS) is a surgery used in the treatment of movement disorders. It involves surgical placement of electrodes in the brain that are connected to a battery-powered stimulator to regulate brain activity. DBS has been used successfully in the management of Parkinson's disease (PD). It has improved patients' movement and quality of life. However, one inconvenience is the limited battery life and the need for battery change to prevent deterioration in function. In this audit, we measured the longevity of DBS batteries in PD at a tertiary neurosurgical centre. Method: A retrospective audit on the longevity of DBS batteries in 86 Patients with PD. We collected data on; date and position of device implant, type of battery used (rechargeable vs non-rechargeable), and the two most recent battery changes. We excluded battery changes that were due to infection. Results: 86 patients had DBS batteries. 21 patients had rechargeable batteries (Abbot Brio, Medtronic Activa RC and Boston Gevia), and 65 had non-rechargeable batteries (Abbot Infinity, Abbot Libra XP, Medtronic Activa PC). 53 patients have undergone a battery change, 49 of those were non-rechargeable batteries. Average battery life of non-rechargeable batteries was 3.06 ± .55 years in Infinity (n = 16), 4.0 ± 1.7 years in Libra XP(n = 22), and 4.6± .9 years in Activa PC (n = 11). Conclusions: All three types of non-rechargeable batteries are lasting less than five years. Activa PC batteries had the lengthiest battery life of 4.6± .9 years, while infinity had the shortest battery life of 3.06± .55 years.